2015
DOI: 10.1007/s00787-015-0759-4
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of BDNF Val66Met genotype and trauma on limbic brain anatomy in childhood

Abstract: Childhood trauma is a major precipitating factor in psychiatric disease. Emerging data suggest that stress susceptibility is genetically determined, and that risk is mediated by changes in limbic brain circuitry. There is a need to identify markers of disease vulnerability, and it is critical that these markers be investigated in childhood and adolescence, a time when neural networks are particularly malleable and when psychiatric disorders frequently emerge. In this preliminary study, we evaluated whether a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
(79 reference statements)
4
12
0
Order By: Relevance
“…Further, we observed volumetric differences only in the right hippocampus, which may be a feature of asymmetric hippocampal structure development as young infants have been previously reported to have a larger right hippocampus, an asymmetry not found in adults (Thompson et al , 2009). Indeed, our finding is consistent with (Marusak et al , 2015), who found larger right (only) hippocampal volume for children, who were Met carriers. Developmental changes in hippocampal volume may reflect general u-shaped developmental trajectories of subcortical volumes which peak in adolescence (Giedd et al , 1999, Giedd & Rapoport, 2010, Wierenga et al , 2014), as well as, variable expression of BDNF over the lifespan (Webster et al , 2006).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Further, we observed volumetric differences only in the right hippocampus, which may be a feature of asymmetric hippocampal structure development as young infants have been previously reported to have a larger right hippocampus, an asymmetry not found in adults (Thompson et al , 2009). Indeed, our finding is consistent with (Marusak et al , 2015), who found larger right (only) hippocampal volume for children, who were Met carriers. Developmental changes in hippocampal volume may reflect general u-shaped developmental trajectories of subcortical volumes which peak in adolescence (Giedd et al , 1999, Giedd & Rapoport, 2010, Wierenga et al , 2014), as well as, variable expression of BDNF over the lifespan (Webster et al , 2006).…”
Section: Discussionsupporting
confidence: 93%
“…In sum, the juxtaposition of our findings and those from the adult literature, in particular studies by Marusak et al (2015) and Hashimoto et al (2016), suggests that the BDNF Val 66 Met polymorphism exerts a significant influence on the cortical and subcortical structures of the brain, but does so differently in children and adults. These differences are likely driven by developmental differences in both structural brain development and BDNF expression, and suggest the need for more research on gene-brain relationships that take a developmental approach.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Intraclass correlation coefficient (ICC) was computed using the total number of voxels in each brain mask; reliability was confirmed by ICC > 0.9. Whole-brain masks and MR image volumes were then processed using BrainSuite to produce participant-specific segmentation of brain areas and derive total GMV of regions of interest (ROIs) in left and right hemispheres (additional detail provided in Supplemental Material; see also Marusak, Kuruvadi, et al, 2015). The amygdala was selected as an a priori ROI.…”
Section: Methodsmentioning
confidence: 99%